Searching for Myself: Motivations and Strategies for Self-Search - Marshall, Cathy; Lindley, Siân (Proceedings of CHI 2014, 2014)
We present findings from a qualitative study of self-search, also known as ego or vanity search. In the context of a broader study about personal online content, participants were asked to search for themselves using their own computers and the browsers and queries they would normally adopt. Our analysis highlights five motivations for self-search: as a form of identity management; to discover reactions to and reuse of user-generated media; to re-find personal content; as a form of entertainment; and to reveal lost or forgotten content. Strategies vary according to motivation, and may differ markedly from typical information-seeking, with users looking deep into the results and using image search to identify content about themselves. We argue that two dimensions underpin ways of improving self-search: controllability and expectedness, and discuss what these dimensions imply for design.